Clinical evaluation of a low-cost robot for use in physiotherapy and gait training. (January 2017) - Volpini, Mariana; Bartenbach, Volker; Pinotti, Marcos; Riener, Robert
Background: Robotic-assisted gait training, a viable and promising therapeutic option for neurological rehabilitation, is not widely adopted in developing countries because of its high cost. In this paper, we describe the concept and construction of a low-cost robot prototype to restore walking ability in children with neurological dysfunction. Methods: The proposed robot consists of an orthosis, a treadmill, a body weight support system and two ankle guidance systems that move the ankles along a physiological kinematic trajectory. The spatiotemporal gait parameters of 60 children with typical development and children with cerebral palsy (aged 7–10 years) were obtained through clinical tests and compared with those provided by the robot. Results: The robotic orthosis presents normative values for stride length, step length and cadence during the typical development of children's gait speed and allows speed adjustments according to the degree of neuromotor impairment. Conclusion: The results evidence the high feasibility of developing a low-complexity rehabilitation device compliant with the physiological trajectory of the ankle as well as with several other physiological gait parameters.